Políticas de educação para a infância : concepções subjacentes à legislação - Oliveira, Graziela Zaltron de (2010)
This research focus on education policies for children and the concepts underlying the Brazilian legislation on the subject. The text is intended to clarify the concept of childhood which supports the Brazilian educational policies aimed at children and to evaluate the pedagogical role of the State in working with children. It is a bibliographical study that covers the history of childhood and discusses the different approaches found in the current legislation documents, relating them to the philosophical concept of becoming. The main topic for analysis, beyond the official documents and governmental policies are Ariès, Heywood, Corazza, Agamben and Kohan,The research results point to the need for better preparation of the childhood conception in the documents which guide the public policies of early childhood education in the country and the challenge of developing a policy for initial and continuing teacher training so that it exceeds the limits currently in effect, paying attention to the need for a deeper understanding of the issue concerning children in their psychological and sociocultural aspects